2015
DOI: 10.1159/000434690
|View full text |Cite
|
Sign up to set email alerts
|

Off-Hour Admission and Outcomes in Patients with Acute Intracerebral Hemorrhage in the INTERACT2 Trial

Abstract: Background: Conflicting data exist of an association between off-hour (weekend, holiday, or night-time) hospital admission and adverse outcome in intracerebral hemorrhage (ICH). We determined the association between off-hour admissions and poor clinical outcome, and of any differential effect of early intensive blood pressure (BP) lowering treatment between off- and on-hour admissions, among participants of the Intensive BP Reduction in Acute Cerebral Hemorrhage Trial (INTERACT2). Methods: Subsidiary analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Bold values are significant, italic values show a statistical trend (i.e., p < 0.1). flammation was significantly associated with unfavorable outcome [16,33,34] ; however, we did not identify NLR as an independent predictor for outcome in ICH [6,16] , which is in line with data from INTERACT2 [18,35] . Regarding functional outcome and its possible relation to hematoma enlargement, Morotti et al [19] -contrary to this study -found associations of higher neutrophil counts with reduced risk of hematoma expansion.…”
Section: Discussionsupporting
confidence: 86%
“…Bold values are significant, italic values show a statistical trend (i.e., p < 0.1). flammation was significantly associated with unfavorable outcome [16,33,34] ; however, we did not identify NLR as an independent predictor for outcome in ICH [6,16] , which is in line with data from INTERACT2 [18,35] . Regarding functional outcome and its possible relation to hematoma enlargement, Morotti et al [19] -contrary to this study -found associations of higher neutrophil counts with reduced risk of hematoma expansion.…”
Section: Discussionsupporting
confidence: 86%
“…Yet, as demonstrated here, BP and OAC reversal treatment appear sufficiently established resulting in similar rates of hematoma enlargement, and related clinical outcomes, in on vs. off-hour-admitted OAC-ICH patients. These data are in line with findings from primary spontaneous ICH patients of the INTERACT2 trial (OAC-ICH < 4%) verifying that off-hour admission was not associated with an increased risk for major disability or mortality [16,25]. With regard to the specific BP and anticoagulation reversal management, all patients showed a significant reduction in systolic BP levels from admission to 4 h which remained stable thereafter, indicating established treatment standards at participating institutions that sufficiently work in off-hours.…”
Section: Discussionsupporting
confidence: 84%
“…On-hour admission was defined as hospital admission within regular working hours (8: 30 a.m. to 4: 30 p.m.) on weekdays. Off-hour hospital admission was defined as admission outside regular working hours on weekdays, weekends (Saturday and Sunday), and public holidays [16].…”
Section: Data Acquisition and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the last few years, concomitant diseases for stroke have become a major theme of discussion, for example, stroke and cancer [16] or stroke and kidney diseases [17,18]. Stroke researchers and clinicians have to deal with local health networks [19,20], in- and pre-hospital patient triages [21,22] and stroke patients have to be identified while they are being treated for other diseases [23]. Acute stroke treatment now predominantly includes the time in an intensive care unit and we published some interesting manuscripts about this aspect [24,25,26,27].…”
mentioning
confidence: 99%